Dlx3 and GCM‐1 functionally coordinate the regulation of placental growth factor in human trophoblast‐derived cells. Issue 10 (1st March 2017) - Li, Sha; Roberson, Mark S.
Abstract : Placental growth factor ( PGF ) is abundantly expressed by trophoblast cells within human placentae and is important for trophoblast development and placental vascularization. Circulating maternal serum levels of PGF are dynamically upregulated across gestation in normal pregnancies, whereas low circulating levels and placental production of PGF have been implicated in the pathogenesis of preeclampsia and other gestational diseases. However, the underlying molecular mechanism of regulating PGF expression in the human placenta remains poorly understood. In this study, we demonstrated that transcription factors Distal‐less 3 (DLX3) and Glial cell missing‐1 (GCM1) were both sufficient and required for PGF expression in human trophoblast‐derived cells by overexpression and knockdown approaches. Surprisingly, while DLX3 and GCM1 were both positive regulators of PGF, co‐overexpression of DLX3 and GCM1 led to an antagonist effect on PGF expression on the endogenous gene and a luciferase reporter. Further, deletion and site‐directed mutagenesis studies identified a novel regulatory element on the PGF promoter mediating both DLX3‐ and GCM1‐dependent PGF expression. This regulatory region was also found to be essential for the basal activity of the PGF promoter. Finally, Chromatin‐immunoprecipitation (ChIP) assays revealed colocalization of DLX3 and GCM1 at the identified regulatory region on the PGF promoter. Taken together, our studies provide important insights into intrinsic regulation of human placental PGF expression through the functional coordination of DLX3 and GCM1, and are likely to further the understanding of pathogenesis of PGF dysregulation in preeclampsia and other disease conditions. Abstract : Our studies examine the role and requirement for the transcription factors Dlx3 and GCM‐1 in the regulation of placental growth factor (PGF) in human placental trophoblast cell lines. Extensive over‐expression and knockdown studies reveal a requirement for both factors; however, the combined action of Dlx3 and GCM‐1 is antagonistic to PGF expression. Our studies identify a novel cis‐acting regulatory element in the proximal region of the PGF gene promoter that binds both factors and is required for the antagonist effects of Dlx3 on GCM‐1.